A Cross-Sectional Survey of Occupational Therapy Education in Saudi Arabia: Challenges and Prospects (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Occupational therapy is an important part of health care that helps people become moreindependent and improve their quality of life through useful tasks. The goal of this cross-sectional studyis to find out what problems occupational therapy school in Saudi Arabia faces and what its future lookslike. The goal of the study is to find out what problems occupational therapy school programmes inSaudi Arabia have in common. The results of this study will help us learn more about occupationaltherapy schooling in Saudi Arabia and help us figure out how to fix the problems that have been found.The data will also give lawmakers, educators, and other people with a stake in the growth andimprovement of occupational therapy education in the country important information.